Analisis Strategi Pemberdayaan Petani Milenial dalam Budidaya Hortikultura di Kapanewon Patuk Kabupaten Gunungkidul - Althorik Divano Afta; Siti Nurlaela; Elea Nur Aziza (Pusat Riset dan Inovasi Nasional, 2025)
The regeneration of farmers became crucial in improving the competitiveness of the agricultural sector, especially for millennial farmers. However, the empowerment approaches that were implemented had not been fully optimal. Empowerment often focused only on the implementation of government programs without the active involvement of millennial farmers. This study aimed to analyze the factors that influenced the empowerment process of millennial farmers and to formulate strategies that could be applied in Kapanewon Patuk, Gunungkidul Regency. This research employed a qualitative method with a case study approach, involving interviews, observations, and Focus Group Discussions (FGDs). The analysis used was SWOT and QSPM analysis. The results of the study showed that the involvement of successful farmers played an important role in increasing knowledge, skills, and technology adoption among millennial farmers. In addition, strengthening institutions and farmer groups became an effective strategy in supporting the empowerment process. The conclusion of this study confirmed that a participatory model-based empowerment strategy, by optimizing the support of successful farmers and integrating technology, could enhance the sustainability of horticultural farming. The government and agricultural extension workers needed to design a more adaptive approach, utilize the potential for collaboration with various stakeholders, and strengthen marketing networks to improve the competitiveness of millennial farmers